Integration challenges for analytics, business intelligence, and data mining - Azevedo, Ana; Santos, Manuel Filipe (Engineering Science Reference, 2020)
"This book provides insights concerning the integration of data mining in business intelligence and analytics systems, increasing the understanding of using data mining in the context of business intelligence and analytics"--